The Attitude of Muslim Scientists in Facing Technological Progress and Their Responsibility Towards Nature and the Environment - Oihana Febby Iswantoro; Dinan Fadila Ihwan; Didik Himmawan (Konsultan Jurnal Ilmiah Indonesia, 2025)
This article discusses the attitudes of Muslim scientists in facing technological advances and their responsibilities towards nature and the environment. Currently, the Industrial Revolution 4.0 has created a phenomenon in the business world called disruptive innovation, which is an innovation that creates new habits and new industrial networks, which ultimately